Persepsi Mahasiswa Uin Walisongo Terhadap Program Diet Plastik Sebagai Upaya Penyelamatn Ekosistem Laut - Shoimatul Jahra; Mukrromah Norjannah; Ahmad Fauzan Hidayatullah (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2020)
The results show that Indonesia is in the second position as the largest country in the world that contributes waste to the sea. This plastic waste is one of the biggest polluters in the sea which can be a serious threat to marine ecosystems. One of the right treatments is the plastic bag diet. This certainly raises various perceptions among the community as an effort to save the environment. This study aims to determine the perceptions of UIN Walisongo Semarang students on the plastic diet program as an effort to save marine ecosystems. This study used a qualitative descriptive research method, with a data collection instrument in the form of a questionnaire. Based on the research that has been done, the 193 samples obtained indicate that the perception of UIN Walisongo students towards the plastic diet as an effort to save marine ecosystems is very positive and supports this movement. This is evidenced by the knowledge of students about the use of plastics and its dangers, the impact of plastic on marine ecosystems and about the plastic diet program.